2010
DOI: 10.1007/s00421-010-1617-1
|View full text |Cite
|
Sign up to set email alerts
|

Responses of muscle mass, strength and gene transcripts to long-term heat stress in healthy human subjects

Abstract: The present study was performed to investigate the effects of long-term heat stress on mass, strength and gene expression profile of human skeletal muscles without exercise training. Eight healthy men were subjected to 10-week application of heat stress, which was performed for the quadriceps muscles for 8 h/day and 4 days/week by using a heat- and steam-generating sheet. Maximum isometric force during knee extension of the heated leg significantly increased after heat stress (~5.8%, P < 0.05). Mean cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 53 publications
1
66
5
Order By: Relevance
“…Previous study showed that 10-week of heat stress by using the same kind of heating sheet induces hypertrophy as well as increase of force generation of quadriceps muscle in healthy human subjects [16]. The discrepancy of the results from both studies may be due to the differences of heating area and subjects.…”
Section: Effects Of Heat Stress On Skeletal Muscle Mass and Functioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Previous study showed that 10-week of heat stress by using the same kind of heating sheet induces hypertrophy as well as increase of force generation of quadriceps muscle in healthy human subjects [16]. The discrepancy of the results from both studies may be due to the differences of heating area and subjects.…”
Section: Effects Of Heat Stress On Skeletal Muscle Mass and Functioncontrasting
confidence: 46%
“…On the other hand, heat stress is one of hypertrophic stimuli for skeletal muscle [16,17]. It has been proposed that heat stress may be a countermeasure for prevention of muscle atrophy [18].…”
Section: Introductionmentioning
confidence: 99%
“…Goto et al 41 reported similar temperature increases to approximately 388C in the vastus lateralis during repeated bouts of heat treatment with a steam-generating sheet. As did Goto et al, 41 we found Fluidotherapy treatment resulted in an increase in peak temperature but did not produce an HSP response in the gastrocnemius or soleus muscle 24 hours posttreatment. Therefore, these data suggest that modalities capable of producing higher temperatures in shorter amounts of time or that render mechanical changes to the tissues should be used to induce HSP expression.…”
Section: Hsp70 and Hsp27p:tmentioning
confidence: 90%
“…Magnetic resonance imaging of each thigh was obtained by using a 1.5 T superconducting system (EXCELART Vantage 1.5T, Toshiba Medical Systems Co., Tokyo, Japan) to obtain the CSA of quadriceps muscles. The thigh image, obtained at 100 mm proximal to the knee joint, was utilized for calculation of the CSA by using a SCION image (19).…”
Section: Methodsmentioning
confidence: 99%